Penggunaan model problem based learning untuk meningkatkan kemampuan berpikir kritis siswa kelas V Sekolah Dasar - Dedeh Siti Rozakiah Safitri; Galih Dani Septiyan Rahayu; Sofyan Nur Mahardika (COLLASE (Creative of Learning Students Elementary Education), 2026)
The low level of critical thinking in fifth grade elementary school students is caused by a monotonous learning model that is not suitable for fifth grade elementary school students, which causes students to be passive and apathetic in the learning process, which ultimately causes the results obtained in the teaching and learning process to not be optimal. For this reason, researchers conducted Mix Method research with an Explanatory Sequential Design and used the Problem Based Learning model. The instruments he used were tests, student response questionnaires and teacher interviews. The data collection and processing techniques used are quantitative and qualitative. The students who acted as respondents were 20 State Elementary School students in Gunungmasigit Village, Cipatat District, West Bandung Regency. The results of this research show that the Problem Based Learning Model can increase the level of critical thinking of students as shown by the results of observations supported by an increase in Post Test results which increase significantly at the end of the learning process. Keywords: Critical Thinking, Problem Based Learning.